Easily-accessible digital palaeontological databases-a new perspective for the storage of palaeontological information - Wolniewicz, Paweł (Geologos, 2009)
Techniques that allow to render diverse types of palaeontological data as publicly available internet resources are described. In order to develop an easily accessible digital palaeontological database, three steps should be followed: (1) digitization of the studied specimens, (2) acquisition of morphometric data, and (3) contribution of the data to open and searchable geoinformatic (palaeontological) databases. Digital data should be submitted to internet databases that allow a user to fetch various types of information from dispersed sources (semantic web services).